(untitled) (BIRDEM Medical Journal, 2016)
Sinus of Valsalva aneurysm (SVA) is an uncommon cardiac anomaly, usually congenital but may be acquired & rarely ruptures. A 24- year- old male presented with a history of prolonged fever, loss of appetite and significant weight loss along with exertional dyspnoea, palpitation and mild chest pain together with clubbed fingers and toes, mild splenomegaly and a continuous machinery murmur over the left sternal edge with associated thrill. Transthoracic echocardiogram revealed ruptured sinus of Valsalva aneurysm with shunt from aorta to right atrium (RA) and vegetation. He was diagnosed as infective endocarditis with rupture of sinus of Valsalva aneurysm and treated with antibiotics and referred to the cardiothoracic surgeon for repair of ruptured SVA. Birdem Med J 2015; 5(1) Supplement: 52-55